Separação de compostos com atividade antibacteriana obtidos a partir de cultivos de Streptomyces clavuligerus em meio complexo - Bustamante, Maritza Catalina Condori (2009)
The cephamycin C is a natural cephalosporin produced by Streptomyces clavuligerus, of great importance in the pharmaceutical industry; it is a β-lactam antibiotic that acts as an inhibitor of the cellular wall synthesis. Besides some activity against Gram-negative bacteria, the cephamycin C is resistant to the action of β-lactamase enzymes responsible for the resistance to penicillin. The information available in the literature, on the stages of the industrial production process of cephamycin C is scarcely found, studying the production process and the antibiotic separation is essential to provide technology to the production section. The present study aimed to develop alternative protocols to isolate and purify composites produced by Streptomyces clavuligerus DSM 738, such as the cephamycin C and penicillin, which present antibacterial activity. The sequence of purification stages proposed in this work consisted of: 1) Microfiltration of the broth for the separating cells and insoluble solids; 2) Ultrafiltration for the separation of high molecular weight sub products, such as proteins and enzymes; 3) Use of adsorption process with non ionic resin for the broth clarification; and 4) Finally, the hipotese this work, the adsorption process by ionic exchange, for the separation of composites with antibacterial activity, such as cephamycin C and Penicillin N. On the other hand, cephamycin C is not available in the market, being restricted to the industries that possess the production technology. The biological method of choice for the bacteriological activity test was the Escherichia coli ESS bacteria against all β-lactams. RMN-1H analysis showed that the use of the microfiltration and ultrafiltration are essential as first purification stages. The second purification stage with non ionic resin (Amberlite XAD-4) showed to be efficient on retaining pigments, finally, with this clarified broth, it was possible to separate two major and well defined fractions with antibacterial activity, by the use of an anion exchange resin (QXL of Amershan), utilizing NaCl and CH3COONa as mobile phase. Analysis by RMN-1H showed that the first fraction can represent a cephalosporin molecule, such as cephamycin C, among others compounds.